Sistem Informasi Penyewaan Kos Dan Kontrakan Hunikita Di Kabupaten Bangkalan Berbasis Web - Ruth Fiona Ayu Sibarani; Sinta Tridian Galih; Cristeddy Asa Bakti (Jurasik (Jurnal Riset Sistem Informasi dan Teknik Informatika), 2025)
The advancement of information technology in today's digital era has had a significant impact on many aspects of life, including the property sector, particularly in the rental of boarding houses and rented houses. Bangkalan Regency, located on Madura Island and experiencing high demand for housing, still faces challenges in providing information related to rental properties. Until now, such information is generally disseminated through printed media, which has limited reach and is less efficient. This study aims to design and develop a web-based information system for renting boarding houses and rented homes, named Hunikita. The system is developed to assist users in searching, booking, and making rental payments online. Key features include property search based on location and price, direct communication with property owners via WhatsApp, and digital verification of payment proofs. The system was built using the Waterfall development method, which consists of sequential phases: requirements analysis, design, implementation, testing, and maintenance. Black Box Testing was applied during the testing phase, and the results showed that all system features functioned properly. The presence of the Hunikita system is projected to provide an effective and time-efficient solution for the property rental process in Bangkalan Regency, particularly for students, university learners, workers, and the general public. The system is also expected to accelerate transactions and offer convenience for both parties involved tenants and property owners